ANALISIS STRUKTUR KRISTAL LITHIUM OKSIDA DAN NIOBIUM PENTAOKSIDA DENGAN XRD - Nadia Septiani; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Lithium oxide and niobium pentaoxide are materials which are used as lithium niobate. XRD result showed that lithium oxide has anti-flourite (cubic) structure with lattice parameter of a is 4.617 Å. Niobium pentaoxide has monoclinic structure and lattice parameter of a is 18.5070 Å, b is 7.7679 Å and c is 17.5994 Å.Keywords: crystal structure ,lattice parameter, lithium oxide, niobium pentaoxide, XRD.